2019
DOI: 10.1111/jvh.13079
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ruzasvir 60 mg and uprifosbuvir 450 mg for 12 weeks in adults with chronic hepatitis C virus genotype 1, 2, 3, 4 or 6 infection

Abstract: In clinical trials, the three-drug regimen of ruzasvir (RZR) 60 mg, uprifosbuvir (UPR) 450 mg and grazoprevir 100 mg, with or without ribavirin, has demonstrated promising efficacy and excellent tolerability across a wide range of hepatitis C virus (HCV)infected individuals. The present study assessed the efficacy and safety of the two-drug combination of RZR 60 mg plus UPR 450 mg administered for 12 weeks in participants with HCV genotype (GT) 1-6 infection. In this open-label clinical trial, treatment-naive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…found to be highly effective, but only for certain genotypes (32). Unfortunately, at the onset of this study, we did not have access to ruzasvir, so we instead tested the combination of uprifosbuvir with the NS5A inhibitor elbasvir.…”
Section: Resultsmentioning
confidence: 99%
“…found to be highly effective, but only for certain genotypes (32). Unfortunately, at the onset of this study, we did not have access to ruzasvir, so we instead tested the combination of uprifosbuvir with the NS5A inhibitor elbasvir.…”
Section: Resultsmentioning
confidence: 99%
“…In the current trial, we hypothesized that an increased dose of ruzasvir would overcome the lower efficacy in individuals with HCV GT3 infection observed in C‐BREEZE‐1 . However, we observed that the ruzasvir 180 mg dose used in the present study did not result in higher efficacy in participants with GT3 infection compared with the 60‐mg dose of ruzasvir used in C‐BREEZE‐1 (SVR12 rates of 77% and 73.8%, respectively) . It is possible that a plateau was reached on the dose‐response curve such that increasing the dose of ruzasvir did not result in any increase in efficacy for GT3 infection.…”
Section: Discussionmentioning
confidence: 64%
“…The C‐BREEZE‐1 trial of ruzasvir 60 mg plus uprifosbuvir 450 mg did not show pangenotypic activity; SVR12 rates were high among those with HCV GT1a (96%; 52/54), GT1b (100%; 15/15), GT2 (97% 28/29) and GT4 infection (90%; 18/20), with lower efficacy in those with GT3 (77%; 33/39) and GT6 infection (67%; 2/3) . In the phase II C‐CREST trials, the three‐drug regimen of ruzasvir 60 mg and uprifosbuvir 450 mg in combination with grazoprevir 100 mg, with or without ribavirin, resulted in SVR12 rates of >90% in a broad patient population with HCV GT1, GT2, GT3, GT4 or GT6 infection .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In part A of the phase 2 C-CREST-1 and C-CREST-2 trials that investigated a 3-drug combination over an 8-week treatment duration, the combination of grazoprevir (100 mg), uprifosbuvir (450 mg), and ruzasvir (60 mg) was selected for further testing over the combination of grazoprevir, uprifosbuvir, and elbasvir (50 mg), as the former consistently resulted in higher 12-week SVR (SVR12) rates in HCV genotypes, including GT2 (27). In the phase 2 C-BREEZE trial, the combination of ruzasvir (60 mg) and uprifosbuvir, an NS5B polymerase prodrug (450 mg), administered once daily for 12 weeks resulted in a 100% SVR among GT2-infected patients (28). It seems reasonable to conclude that the success of the trial was, in part, due to the activity of ruzasvir in GT2.…”
Section: Discussionmentioning
confidence: 99%